Scientific Literacy in Pacu Jalur Competition Students of SMA Negeri 1 Teluk Kuantan - Saribatul Islamia; Yennita Yennita (Journal of Indonesian Science Teachers, 2023)
Scientific literacy of Pacu Jalur is the ability to understand physics concepts and processes integrated into local culture and wisdom in Rantau Kuantan, Riau. The Pacu jalur competition is one of the cultures that has existed for generations in Teluk Kuantan, Riau and it has been identified that the Pacu jalur competition has scientific potential that can be explained scientifically. This research aims to identify the level of physics literacy in the Pacu Jalur Competition for students of SMA Negeri 1 in Teluk Kuantan. For this purpose, the type of research used is survey research with a quantitative descriptive approach. The sample in the study was 170 students consisting of 55 male students and 115 female students. The instrument in the study was a physics science literacy test on Pacu Jalur which consisted of 7 multiple choice items with a reliability coefficient of KR-20 of .86. Descriptive analysis techniques were used to obtain the level of literacy in the Physics of Pacu Jalur in the sub-context of the Pacu Jalur competition. The results of the descriptive and inferential analysis show that the physics literacy level of Pacu Jalur students has an average total score of 33.73. Based on gender, it was identified that male students had better physics science literacy skills than female students with an average score of 34.54 for male students while 32.92 for female students. However, the differences in scores based on gender are not significant. Overall, it can be concluded that the physics literacy level of SMA Negeri 1 Teluk Kuantan students in the Pacu Jalan competition is still in the very low category and gender does not affect the level of scientific literacy of students.